Porous titanium scaffolds modified with Zeolitic Imidazolate Framework (ZIF-8) with enhanced osteogenic activity for the prevention of implant-associated infections - Di Matteo, Valentina; Di Filippo, Maria Francesca; Ballarin, Barbara; Bonvicini, Francesca; Iaquinta, Maria Rosa; Panzavolta, Silvia; Mazzoni, Elisa; Cassani, Maria Cristina (Frontiers in Chemistry, 2024)
In this study, Zeolitic Imidazolate Framework 8 (ZIF-8) was coated on porous Ti6Al4V scaffolds, either bare or previously modified with Hydroxyapatite (HA) or HA and Gelatin (HAgel), via a growing single-step method in aqueous media using two contact times at 6 h and 24 h. The coated scaffolds termed ZIF-8@Ti, ZIF-8@HA/Ti and ZIF-8@HAgel/Ti were characterized by using scanning electron microscopy (SEM), powder X-ray diffraction (PXRD), Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) and Molecular Plasma-Atomic Emission Spectroscopy (MP-AES). In order to assess the cell proliferation rate, the cytocompatibility of the scaffolds was evaluated in primary osteoblasts (hOBs) using Alamar Blue assay whilst the osteoconductivity was analyzed in hOBs using Real-Time approach, evaluating the expression of Secreted Phosphoprotein 1 (SPP1). Osteopontin, which is the protein encoded by this gene, represents the major non-collagenous bone protein that binds tightly to HA. The scaffolds were shown to be non-cytotoxic based on hOB proliferation at all time-points of analysis (24 h and 72 h). In hOB cultures, the scaffolds induced the up-regulation of SPP1 with different fold-changes. Some selected scaffolds were assayed in vitro for their antibacterial potential against Staphylococcus epidermidis; the scaffolds coated with ZIF-8 crystals, regardless the presence of HA and Gelatin, strongly inhibited bacterial adhesion to the materials and reduced bacterial proliferation in the culture medium demonstrating the suitable release of ZIF-8 in a bioactive form. These experiments suggest that the innovative scaffolds, tested herein, provide a good microenvironment for hOBs adhesion, viability, and osteoconduction with effective prevention of S. epidermidis adhesion.